2003
DOI: 10.1017/s1014233900001607
|View full text |Cite
|
Sign up to set email alerts
|

The Gir cattle breed of India - characteristics and present status

Abstract: SummaryThe Gir is a famous milk cattle breed of India. The native tract of the breed is Gir hills and forests of Kathiawar including Junagadh, Bhavnagar, Rajkot and Amreli districts of Gujarat. The breeding tract lies between 20°5’ and 22°6’ north latitude and 70° and 72° east longitude. The total cattle population of Saurashtra region i.e., breeding tract of Gir cattle is 2.5 million and Gir breed accounts for 37 percent of total cattle population in the region. The body of Gir animals is well proportioned. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
4
19
5
1
Order By: Relevance
“…Rabeya et al (2009) also worked on the same cattle and were obtained 76.2±4.0 and 73.2±3.3 kg yearling weight for male and female, respectively. Guar et al (2003) reported the mean yearling weight for Gir male and female was 138.5±0.52 and 135.7±5.7 Kg, respectively and overall mean yearling weight was 137.0±4.9 kg. The yearling weight of Brahman crossed calves was larger resembling the findings from different workers stated above.…”
Section: Yearling Weightmentioning
confidence: 95%
“…Rabeya et al (2009) also worked on the same cattle and were obtained 76.2±4.0 and 73.2±3.3 kg yearling weight for male and female, respectively. Guar et al (2003) reported the mean yearling weight for Gir male and female was 138.5±0.52 and 135.7±5.7 Kg, respectively and overall mean yearling weight was 137.0±4.9 kg. The yearling weight of Brahman crossed calves was larger resembling the findings from different workers stated above.…”
Section: Yearling Weightmentioning
confidence: 95%
“…In earlier studies of Indian native cattle, the major focus was on assessment of morphological parameters and information gained from local sources (Nivsarkar et al 2000;Joshi et al 2001;Singh et al 2002;Gaur et al 2003;Karthickeyan et al 2006). Recently, assessment of genetic diversity and delineation of the genetic structure of cattle breeds have become a major concern, as some of the important populations and breeds are either declining or breed characters are being diluted under the present production system.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, categorization of these cattle breeds has often been based on morphological data and information gained from the local breed keepers. 1,[4][5][6][7] Hence, an effort to deduce the genetic structure among the Indian native cattle breeds becomes pertinent for the development of future management strategies. For this purpose, microsatellites markers previously exploited for diversity studies in cattle populations from Africa, Europe, and Asia [8][9][10][11][12][13][14] are utilized herein to characterize Indian native cattle breeds.…”
mentioning
confidence: 99%